2023
DOI: 10.1186/s13098-023-01006-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metabolic dysfunction-associated fatty liver disease and diabetic kidney disease on the risk of hospitalization of heart failure in type 2 diabetes: a retrospective cohort study

Abstract: Background Diabetes mellitus is a major risk factor for heart failure. A recent consensus statement recommended annual cardiac biomarker testing (e.g. natriuretic peptide or high-sensitivity cardiac troponin) for all patients with diabetes. We aimed to identify patients at a higher risk of hospitalization for heart failure among patients with type 2 diabetes to prioritize those who would require screening. Methods Overall, 1,189,113 patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(60 reference statements)
1
1
0
Order By: Relevance
“… 38 , 39 Moreover, previous research reported that the CRS association was dependent on hypertriglyceridemia and oxidative stress. 40 Lee et al 41 observed that proteinuria and renal dysfunction were risk enhancers for hospitalization for HF in T2DM patients, which was in line with previous studies. 42 Also, in patients without proteinuria and decreased eGFR, MAFLD significantly increased the risk of hospitalization for HF, signifying that active diagnostic and interventional policies should be available for T2DM patients, minimally in those who concurrently have diabetic kidney disease or MAFLD.…”
Section: Discussionsupporting
confidence: 84%
“… 38 , 39 Moreover, previous research reported that the CRS association was dependent on hypertriglyceridemia and oxidative stress. 40 Lee et al 41 observed that proteinuria and renal dysfunction were risk enhancers for hospitalization for HF in T2DM patients, which was in line with previous studies. 42 Also, in patients without proteinuria and decreased eGFR, MAFLD significantly increased the risk of hospitalization for HF, signifying that active diagnostic and interventional policies should be available for T2DM patients, minimally in those who concurrently have diabetic kidney disease or MAFLD.…”
Section: Discussionsupporting
confidence: 84%
“…Cardiac fibroblasts (CFs) are one of the main effectors in fibrotic scar formation in the heart, owing to their role in ECM turnover [ 8 ]. When myocardial fibrosis occurs, CFs proliferation, migration, phenotypic transformation, and collagen secretion significantly increase [ 9 , 10 ]. The differentiation of CFs into myofibroblasts is a crucial process in myocardial fibrosis, with α-smooth muscle actin (α-SMA) considered a marker of myofibroblast differentiation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%